SELECTION OF TELECOMMUNICATION EQUIPMENT IN VOICE MESSAGE TRANSMISSION SYSTEMS - PIDCHENKO, SERGIY; KUCHERUK, OKSANA; PYVOVAR, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Today, there is a wide range of telecommunications equipment from various manufacturers that performs similar functions in telecommunications networks. Taking into account the high cost of modern telecommunications equipment, the problem of making decisions on the optimal composition of telecommunications network equipment becomes important and relevant.When choosing the appropriate telecommunication network equipment, it is necessary to make a decision taking into account a set of criteria that contradict each other. One of the promising approaches to solving such problems is the use of MCDM (Multiple Criteria Decision Making) methods.  MCDM methods help to improve the efficiency of the decision-making process and avoid certain mistakes when choosing telecommunications equipment. In particular, the study considers the problem of choosing a voice message codec based on a set of criteria. An important step in the multi-criteria decision-making process is to determine the weights of the criteria. In previous studies, the authors considered the issue of determining the weights of the criteria. A significant number of MCDM methods have been developed to determine the best alternative, but under certain conditions, the use of these methods can give different results. Therefore, scientists usually use more than one method at the same time.In this study, TOPSIS, MARCOS, and PIV methods were used to select the appropriate codec configuration in order to obtain the results of codec ranking in the most objective way. The ranking of speech message codecs by the three methods was obtained. The obtained results are compared with each other. The best alternative is determined. The thesis that it is necessary to use more than one method when ranking and choosing the best alternative is confirmed.
Keywords: telecommunication networks; MCDM methods; multi-criteria selection; TOPSIS; PIV; MARCOS